PEMODELAN HARGA SAHAM BLUE CHIP MENGGUNAKAN VECTOR AUTOREGRESSIVE (VAR) - Agus Suharsono; Aryo Wibisono (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2016)
In a stock exchange in the capital market, the most in demand by investors is stocks. Shares are securities which shows the ownership of the company, so that shareholders have the right to a dividend or other distribution of profit sharing as well as by the company to its shareholders. The capital market is an indicator of economic progress and support the economy of a country. In this decade, the stock market has experienced rapid development due to pressure from technological change, liberalization and globalization. These changes affect the behavior of the capital markets and cause long-term balance and improving the relations between the world's capital markets. Otherwise interconnected capital markets if the two separate markets have the same movement and the correlation between the movement of the index. Capital markets in the region are likely to have the same movement and the effects of contagion (contagion effect) is high (1). During the observation period, October 2015 to March 2016, there was a phenomenon in which IHSG is not always the same and has a correlation with the movement of world stock market indices. It is also supported by the differences found in the results of some previous studies. The purpose of this study was to determine the relationship between stocks bluechip : Astra International Tbk (ASII), Unilever Indonesia Tbk (UNVR), Astra Agro Lestari Tbk (AALI), Bank Rakyat Indonesia Agroniaga (AGRO) and Bank Rakyat Indonesia (BRI ). The analytical method used in this study is Multivariate Time Series, especially Vector Autoregression (VAR). The results of this study with the model produces the best model VAR (2), AGRO = 11.56 - 4.03*ASII(-1) - 4.40*ASII(-2) + 3.76*UNVR(-1) + 1.27*UNVR(-2) + 1.38*AALI(-1) + 2.54*AALI(-2) + 0.73*AGRO(-1) + 0.14*AGRO(-2) + 5.40*BRI(-1) - 1.34*BRI(-2). The value of AIC (Akaike Information Criterion) = 4.47 Keywords: BLUE CHIP, Stock Price, VAR.